AGRICULTURAL DIGITALIZATION: STRATEGIES FOR IMPROVING HARVEST QUALITY AND FARMER WELFARE IN INDONESIA - Amruddin; Fitriah Suryani Jamin; HM. Saiful Bahri; Taransa Agasya Tutupoly; Emmy Hamidah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to determine (1) the potential for agricultural digitalization in Indonesia; and (2) strategies to improve harvest quality and farmer welfare in Indonesia through agricultural digitalization. This research is qualitative- descriptive research. The results of this research show that (1) Agricultural digitalization has the potential to change farmers' mindsets in order to maximize and utilize the digital era so that it can encourage farmer independence. The government needs to prepare superior human resources in utilizing agricultural digitalization supported by Indonesia's abundant diversity of agricultural products; and (2) agricultural digitalization strategies to improve harvest quality and farmer welfare in Indonesia, including the SO strategy through promoting agricultural digitalization to improve harvest quality and farmer welfare, the WO strategy by developing the concept of agricultural digitalization (digitalization of agricultural processing and marketing), the ST strategy through work cooperation between the government and agricultural stakeholders supports agricultural digitalization, and WT's strategy is to educate agricultural product business actors to utilize agricultural digitalization.